Exploring the relationship between anorexia and awareness towards pro-ana websites among the UiTM students at Akasia College / Rashidah Rozi - Rozi, Rashidah (2002)
With the sophisticated technology nowadays, the world has been introduced to the high-speed information provider, known as Internet. With its great speed and its role of delivering information, Internet has been mis-used by some people. With Internet, websites are developed to fulfill this urgency. The creation of websites leads us to the creation of 'pro-ana' websites, where these sites promote anorexia, an eating disorder as a good thing. The study undertaken is to determine whether the studies on the exploring of the relationship between anorexia and awareness towards pro-ana websites among the UiTM students at, Akasia College, section 18, Shah Alam, Selangor Darul Ehsan. At the same time, it is also to know the students feedback on this matter. The students involved in this research are chosen specifically from Block 6 and Block 9 of Akasia College.